Polarizability of Kr6+ from high-L Kr5+ fine-structure measurements - Lundeen, S. R.; Fehrenbach, C. W. (My University, 2007)
The transition between n=55 and n=109 Rydberg levels of Kr5+ has been studied at high resolution using the resonant excitation stark ionization spectroscopy method. Resolved excitation of L=6, 7, 8, and 9 levels in n=55 lead to a determination of the fine-structure energies of these levels. Interpreted with the long-range polarization model, this leads to a measurement of the dipole polarizabilities of Zn-like Kr6+, αd=2.69(4)a30. Obtaining a value of the quadrupole polarizability from the data will require additional theoretical input. Factors contributing to the signal and noise levels in measurements of this type are discussed.